Microglial cell activation is a source of metalloproteinase generation during hemorrhagic transformation - del Zoppo, Gregory J (Nature Publishing Group, 2012)
Hemorrhage and edema accompany evolving brain tissue injury after ischemic stroke. In patients, these events have been associated with metalloproteinase (MMP)-9 in plasma. Both the causes and cellular sources of MMP-9 generation in this setting have not been defined. MMP-2 and MMP-9 in nonhuman primate tissue in regions of plasma leakage, and primary murine microglia and astrocytes, were assayed by immunocytochemistry, zymography, and real-time RT-PCR. Ischemia-related hemorrhage was associated with microglial activation in vivo, and with the leakage of plasma fibronectin and vitronectin into the surrounding tissue. In strict serum-depleted primary cultures, by zymography, pro-MMP-9 was generated by primary murine microglia when exposed to vitronectin and fibronectin. Protease secretion was enhanced by experimental ischemia (oxygen-glucose deprivation, OGD). Primary astrocytes, on each matrix, generated only pro-MMP-2, which decreased during OGD. Microglia–astrocyte contact enhanced pro-MMP-9 generation in a cell density-dependent manner under normoxia and OGD. Compatible with observations in a high quality model of focal cerebral ischemia, microglia, but not astrocytes, respond to vitronectin and fibronectin, found when plasma extravasates into the injured region. Astrocytes alone do not generate pro-MMP-9. These events explain the appearance of MMP-9 antigen in association with ischemia-induced cerebral hemorrhage and edema.